An Evaluation of Christian Education in Indonesia in light of Targum: A Cognitive Psychology Approach - Frederich Oscar Lambertus Lontoh; Philip Suciadi Chia (Pharos Journal of Theology, 2023)
Education is an important matter in Indonesia and also globally. This importance of education is ingrained in the Indonesian Law Constitution in 1945 (Undang-Undang Dasar 1945), chapter 31 where it states that: every Indonesian citizen deserves to receive education, and is obliged to attend basic education and the government is obliged to pay for it. In addition, the government is to seek and organize a national education system which increases faith and piety as well as noble character in the context of educating the life of the nation, which is regulated by law. The state prioritizes the education budget of at least twenty percent of the state revenue and expenditure budget as well as from the regional revenue and expenditure budget to meet the needs of implementing national education. It alsoadvances science and technology by supporting high religious values and national unity for the advancement of civilization and the welfare of mankind. As a result, the Indonesian government provides a free of charge education at public schools from grades one to nine to give an opportunity of equal education to every citizen which includes nine subjects. The challenge, however, is that all students in the public schools are required to take nine subjects every academic year. This could be overwhelmingly difficult for the students both academically and also mentally. Thus, this article attempts to propose a solution academically as to how students could cope with their forgetfulness to achieve the maximum grades. This solution, it is argued, can be discovered in the Targum and is tested through a cognitive psychology approach. Targums which form a part of the Jewish traditional literature from the Second Temple period are not merely a translation of the Hebrew Torah text into Aramaic, but also possess immense Talmudic wisdom that illuminates the Biblical stories but also provide us with important tried and tested lessons for today.